2010
DOI: 10.1159/000279322
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Hydroxylase as Novel Target for the Treatment of Depressive Disorders

Abstract: Serotonin (5-HT) is a monoamine implicated in a variety of physiological processes that functions either as a neurotransmitter or as a peripheral hormone. Pharmacological and genetic studies in humans and experimental animals have shown that 5-HT is important for the pathophysiology of depressive disorders. The 5-HT system is thus already a main target for the therapy of these diseases. The peripheral and cerebral biosynthesis of 5-HT is initiated by two distinct tryptophan hydroxylases: TPH1 and TPH2. This du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 367 publications
2
47
0
Order By: Relevance
“…TPH is a rate-limiting enzyme that plays a vital role in the biosynthesis of 5-HT (Matthes et al, 2010). In the present study, we showed that TPH-positive cells were mainly localized to the dorsal raphe nucleus, the largest serotonergic nucleus, in rats.…”
Section: Discussionsupporting
confidence: 59%
“…TPH is a rate-limiting enzyme that plays a vital role in the biosynthesis of 5-HT (Matthes et al, 2010). In the present study, we showed that TPH-positive cells were mainly localized to the dorsal raphe nucleus, the largest serotonergic nucleus, in rats.…”
Section: Discussionsupporting
confidence: 59%
“…Although not shown in the present study, insufficient tph2 or lack of serotonin has been shown to lead to mood disorders such as depression [30], schizophrenia [31] and neurodegeneration such as Alzheimer’s dementia [32], [33]. Our mRNA expression study clearly demonstrated that unloading-induced tph2 deficiency is prevented by pre-application of knee loading.…”
Section: Discussionsupporting
confidence: 39%
“…However, currently the attempts of manipulation with dietary tryptophan for therapeutic effect were not impressive and the clinical value of TPH2 as a target for psychotropic drugs is lower compared with SERT or MAOA. However, in perspective, TPH2's value as a target for psychotropic drugs may be increased, when selective TPH2-activating drugs are created [149]. We hope that further study of the TPH2 genetics in humans, mice and other species will increase clinical value of this enzyme as a predictor of affective disorder risk and efficacy of antidepressant drugs.…”
Section: Expert Opinion and Future Directionsmentioning
confidence: 99%